2017
DOI: 10.1016/j.jcot.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outcome of proximal femur locking compression plate (PFLCP) in unstable proximal femur fractures

Abstract: PF-LCP is not recommended as a definitive implant but can be used as an alternative for the treatment of unstable proximal femoral fractures when there is no option available for other routinely used implants. Despite of its complications, PF-LCP is used where all implants fail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
5
12
3
Order By: Relevance
“…In the present study, the mean age was found to be 59.04±18.45 years against 55.3±17.9 years and 59.6 years according to Prabhat et al and Shah et al respectively. 28,29 Our study also showed a bimodal distribution of patients.…”
Section: Discussionsupporting
confidence: 59%
“…In the present study, the mean age was found to be 59.04±18.45 years against 55.3±17.9 years and 59.6 years according to Prabhat et al and Shah et al respectively. 28,29 Our study also showed a bimodal distribution of patients.…”
Section: Discussionsupporting
confidence: 59%
“…Shah MD et al studied 20 patients and reported a mean union time of 18.75 weeks ± 3.67, and they had excellent results in 10 cases and four poor results. The mean Harris hip score was 82 ± 20.54, and they had complications such as four super icial and two deep infections and 2 cases with coxa valga (Shah et al, 2017). In Kumar N et al study of 30 patients, they achieved a union rate of 100% with the meantime to fracture union being nine weeks ranging from 8 to 10 weeks.…”
Section: Resultsmentioning
confidence: 97%
“…Ten (50%) cases had excellent Harris Hip Scores, 3 (15%) cases had good, 3 (15%) cases had fair and 4 (20%) cases had poor functional scores with an average HHS of 80.2 ± 28.54. The complication rate was 45% which included four cases (20%) of superficial infection, two cases (10%) of deep infection and four cases (20%) of late complications including non-union as well as mechanical deformation [15].…”
Section: Discussionmentioning
confidence: 98%